PERAN NOTARIS DALAM PEMBUATAN KONTRAK JUAL BELI YANG BERLEGALITAS DITINJAU DARI PERSPEKTIF HUKUM POSITIF - Nasya Oktavia (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Notary legal services are currently very important and necessary in the buying and selling process. Especially in the process of making a contract which not everyone is able to make. This research aims to analyze the role of notaries in making sales and purchase contracts so that they meet legality requirements in accordance with positive law in Indonesia and explore the importance of legal education for the public in understanding this role. This research uses a normative approach with a literature study method, referring to statutory regulations, legal literature, as well as national and international journals. The research results show that notaries have an important responsibility in ensuring the validity of transactions through making authentic deeds, verifying documents, and providing legal advice. Legal education to the public has also proven crucial to increase awareness of the importance of legality in buying and selling transactions, so as to reduce the potential for disputes and legal problems in the future